2015
DOI: 10.5604/17331331.1185238
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Methods for Identification of Monophasic Salmonella Typhimurium Strains

Abstract: Two molecular biology methods were used to differentiate Salmonella enterica 1,4,[5],12:i:- strains: “Salmonella Check&Trace microarray” (CT) and multiplex PCR (mPCR). For 92 strains in CT result “Salmonella 1,4,[5],12:i:-“ were obtained. Those strains were confirmed in mPCR as monophasic fljB-lack Salmonella Typhimurium. For 17 strains, which in CT assay were recognized as Salmonella Typhimurium, the same identification was obtained in mPCR. Reference Salmonella strains: Lagos, Agama, Tsevie, Glocester a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Lagos. Both results are an improvement in comparison to the study of Madajczak (Madajczak et al, 2015) which showed that CTS assay correctly identified most of the S. Typhimurium and its monophasic variants but failed to recognize S . Agama and S .…”
Section: Discussionmentioning
confidence: 52%
“…Lagos. Both results are an improvement in comparison to the study of Madajczak (Madajczak et al, 2015) which showed that CTS assay correctly identified most of the S. Typhimurium and its monophasic variants but failed to recognize S . Agama and S .…”
Section: Discussionmentioning
confidence: 52%